Malakoplakia among kidney transplant recipients: case series and literature review - Abbasi, Ali B.; Gamino, Gerardo; Zambeli-Ljepović, Alan; Whelan, Adrian M.; Roll, Garrett R.; Altshuler, Peter J. (Frontiers in Immunology, 2025)
We report two cases of malakoplakia after kidney transplant, a rare granulomatous condition that occurs primarily in immunocompromised patients and his thought to occur due to incomplete clearance of phagocytized bacterial residue by macrophages. Both patients were at heightened immunological risk due to being highly sensitized or prior episodes of rejection, both experienced E. Coli infections in the first 4 months after transplant, and both presented with granulomatous masses that were biopsied and confirmed to be malakoplakia. Both were treated with suppressive antibiotics and required urinary drainage of the transplant kidney, resulting in improvements in the size of the mass on imaging. Given that both patients were at heightened immunological risk due to sensitization or episodes of rejection, we sought to investigate whether these are common risk factors for malakoplakia in the published literature. We summarized 59 published reports of malakoplakia in kidney transplant recipients. We found that malakoplakia cases predominantly occur in the first two years after transplant and that 47% of patients had either prior rejection or a prior transplant. We also found that many case reports of malakoplakia involve E. Coli infections and that improvement or resolution of malakoplakia was more common in case reports that did not involve surgical resection of the mass.